2002
DOI: 10.1152/ajpregu.00386.2001
|View full text |Cite
|
Sign up to set email alerts
|

Neural factors account for strength decrements observed after short-term muscle unloading

Abstract: Strength decrements observed after extended (4-6 wk) periods of muscle unloading are associated with significant atrophy. Because early (up to 2 wk) strength gains from resistance exercise are related to improved neural recruitment, we hypothesized that the loss of strength resulting from 2 wk of muscle unloading [unilateral lower limb suspension (ULLS)] was due to impaired neural activation of the affected muscle. Blood samples, muscle biopsy specimens, muscle function data, and electromyography (EMG) recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
133
6
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(161 citation statements)
references
References 18 publications
10
133
6
11
Order By: Relevance
“…Berg et al reported similar results and interestingly found that these changes were completely reversed after 7 weeks of recovery [73]. A reduction of strength power likely caused by altered neural function may precede atrophy in periods of decreased activity [65]. Failure of voluntary activation from the central nervous system to the quadriceps muscle as a result of disruption of the ACL has been implicated [74].…”
Section: Causes Of Quadriceps Weaknessmentioning
confidence: 80%
See 1 more Smart Citation
“…Berg et al reported similar results and interestingly found that these changes were completely reversed after 7 weeks of recovery [73]. A reduction of strength power likely caused by altered neural function may precede atrophy in periods of decreased activity [65]. Failure of voluntary activation from the central nervous system to the quadriceps muscle as a result of disruption of the ACL has been implicated [74].…”
Section: Causes Of Quadriceps Weaknessmentioning
confidence: 80%
“…Decreased levels of physical activity [54][55][56], weightbearing status [56][57][58], and immobilization [59][60][61] can lead to progressive atrophy. Several factors including decreased protein synthesis [62][63][64], increased levels of plasma cortisol [65], arthrogenic inhibition [66,67], and altered afferent inflow [66] may be responsible for atrophy after trauma or in periods of prolonged muscular disuse. Though evidence is lacking, this notion alone supports the possible benefits of prehabilitation in preoperative ACL-deficient patients.…”
Section: Causes Of Quadriceps Weaknessmentioning
confidence: 99%
“…redução na atividade elétrica do TA seja consequência da inibição muscular, que é a incapacidade de ativar ao máximo todas as unidades motoras de um músculo durante o esforço voluntário. Os mecanismos que impedem a ativação completa dos músculos após uma lesão ainda não são bem compreendidos, mas a presença da lesão, o edema, a dor ou até mesmo a apreensão do sujeito (medo de sentir dor ao realizar a contração) pode inibir o limiar de disparo das unidades motoras (28) . Tendo em vista que músculos uniarticulares, com função antigravitacional e composição predominante de fibras lentas aparentemente são os mais afetados pelo desuso (10) , era esperada a redução de ativação EMG do SO.…”
Section: Discussionunclassified
“…Overwintering submergence presents a springtime challenge because disuse of neuromotor processes typically leads to loss-offunction through muscle atrophy and neuroplastic motor defects, especially in humans and laboratory rodents (Bonaldo and Sandri, 2013;Clark et al, 2006;Cormery et al, 2005;Deschenes et al, 2002;Seki et al, 2007). Hibernating, overwintering and estivating vertebrates provide interesting exceptions to this rule as they use integrative mechanisms to curtail muscle atrophy and motor decline during extended inactivity (Hudson and Franklin, 2002).…”
Section: Introductionmentioning
confidence: 99%